Mathematics Professional Development Researchers as Stakeholders - Paola Sztajn (Universidade de Lisboa, 2013)
In this paper I argue that since the publication of The Reflective Practitioner (Schön, 1983), mathematics professional development researchers have focused on bringing teachers' knowledge to the foreground, leaving behind the value of their own research community's knowledge. I revisit Schön's criticism of the technical rationality and use examples from my own practice in mathematics professional development to suggest that instead of continuing to reject technical rationality, mathematics professional development researchers should consider a revised version of it to move the field forward: one that values both teachers' and researchers' knowledge.